PERUBAHAN BAHASA (Interaksi antarkomponen Tatabahasa Bahasa Arab) - Fahmi Gunawan (Sunan Kalijaga State Islamic University Yogyakarta, 2009)
This study aims to analyze the change in Arabic languagethe interaction of its structural components. It is the language change, which causes the change of other structural components. The data is taken from the religious article of al-Ahram magazine. By using Poedjosoedarmo’s point of view, it can be found that the language change (Arabic syntax) occurs because of the movement of the subject of the sentence (Fi’iliyah). In addition, the system of topicalisation will come up, which, in turn, this makes another topic (mubtada) and comment (khabar) on the noun clause (Ismiyyah). The system of topic and comment then make the system of adjustment of number (mutsanna and jamak). and cases (I’rab). All that occurs is the interaction between language component to create the ideal structure, which is clear, compact, and understandable.